Sustainability of Kampung Tua Related to the Existence of Modern Area in Batam City, Indonesia - Fandy Iood; Yusuf Danuwidjojo; Yuanita F.D. Sidabutar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The existence of the old village in Batam City is threatened because of its existence. The development of modern areas such as industry, trade and services, this has an impact on the survival of the old village. Several villages in Batam City such as Kampung tua Melayu, Mangrove Serip, Jabi, Teluk Mata Ikan etc. indicated by the existence of the Old Village Gate which is the identity of the old village. Kampung tua Melayu as it is currently being felt will be eroded by the development of the surrounding area, such as the Modern Area which will gradually eliminate one of the characteristics that exist in the old village as a remnant of local wisdom in the city of Batam. The purpose of this research is to analyze the survival of the old village in Batam City. The research method is a qualitative descriptive method with natural observation and centralized interviews. The result of the research is that the old village can survive if it is developed according to the potential of the area so that it can be interrelated with the existence of a modern area. The modern area has an impact on the old village because it increases the number of immigrants which affects all aspects, while the old village with a Malay identity can be an attraction for the newcomers. From the results of a physical survey of land use, there are several locations in the old village that have begun to change their orientation of function into service and trade land, the function of the building which has turned into a boarding house and a place for trading along with the development of the city of Batam, and the shape of the building that is only slightly in accordance with the shape of the building. houses on stilts according to the history of the area and non-physical forms in the form of community social activities as seen in reduced community activities because the natives are influenced by individualistic immigrants, as well as cultural activities such as top competitions, Jong competitions, kite competitions which are lost in the old village area due to cultural locations were evicted and there was a change in the orientation of Malay identity in the area.